Strengthening Student Character through Philosophical Foundations: A Systematic Literature Review on Pancasila, Idealism, and Realism in Indonesian Education - Sunayah, Sunayah; Angraini, Dewi; Astria, Yeni; Susanti, Yeni; Jelestari, Nerma (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study addresses the growing challenge of character education in the technological era, where rapid social change demands a strong and coherent philosophical foundation for education. The aim of this research is to examine how philosophical schools of thought particularly idealism and realism contribute to student character building, with Pancasila positioned as the national philosophical framework of Indonesian education. This study employs a qualitative approach using a Systematic Literature Review (SLR) method. Relevant articles were collected from reputable academic databases using keywords related to educational philosophy, idealism, realism, character education, and Pancasila. Inclusion and exclusion criteria were applied to select peer-reviewed journals that are relevant to the research focus, resulting in a synthesized analysis of selected studies. The findings indicate that Pancasila serves as a central and integrative philosophical foundation for Indonesian education. Idealism emphasizes universal values and absolute truth, which are essential for character formation, while realism highlights the importance of empirical experience and contextual learning. However, the implementation of these philosophies especially idealism faces significant challenges when they are not deeply integrated into curricula, teacher training, and educational practice. The study concludes that effective character education requires moving beyond philosophical concepts at the theoretical level toward practical, philosophically grounded pedagogical strategies. The novelty of this study lies in its integrative analysis of idealism, realism, and Pancasila within a single SLR framework, while its contribution is to provide a philosophical reference for policymakers and educators in strengthening character education that is contextually relevant and value-oriented in Indonesia.